Consorciação em cafeeiros orgânicos por diferentes períodos com feijão-de-porco ou lablabe - Moreira, Guilherme Musse (2014)
This paper evaluates the effects of the period of intercropping of hyacinth beans (Dolichos lab-lab) and jack beans (Canavalia ensiformis) on coffee (Coffea arabica) growth and productivity. The treatments were the two legume species combined in a factorial design with four intercropping periods (30, 60, 90 e 120 days after planting). The control treatment consisted of plots with coffee sole crop. The experiment was carried out for two years at Rio Pomba, Minas Gerais state, Brazil. The biomass of legumes and the growth and yield of coffee shrubs was quantified in each year. There was a positive linear accumulation of the legume dry matter as intercropping period increased. On the first year, jack beans (2.65 t ha-1) accumulated more biomass than hyacinth beans (1.89 t ha-1). On the second year, hyacinth beans accumulated 5.74 t ha-1 of dry biomass and jack beans 2.89 t ha-1 at 120 days. On the first year, the increasing of intercropping period with hyacinth beans resulted in a decrease of the coffee shrub canopy diameter and number of leaves. On the second year, the coffee shrubs intercropped with hyacinth beans grew more than the ones intercropped with jack beans. Compared to the control treatment, the intercropping reduced coffee yield, presenting different effects on them.